A modified fluorinated gypsum and its preparation method and application
Modified fluorine gypsum is prepared by crushing, screening, aging and mechanical grinding of fluorine gypsum, and mixed with sodium hydroxide and naphthalene-based water reducing agents, the problem of unstable performance of fluorine gypsum is solved, and its effective application in building materials is achieved, reducing construction costs and reducing environmental pollution.
Patent Information
- Application Number
- CN202411949381.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
Untreated fluorine gypsum contains unstable properties, is difficult to dissolve in water, has slow hydration, is low initial strength, and is severely swelled, and cannot be used directly as building materials, resulting in waste of resources and environmental pollution.
Modified fluorine gypsum is prepared by crushing, screening, aging and mechanical grinding, and mixed with sodium hydroxide and naphthalene-based water reducing agent to form modified fluorine gypsum with excellent hydration properties.
After the gel is prepared with water, the initial set time of modified fluorine gypsum is 3h, the final set time is 15h, the flexural strength of 7 days is 3.5MPa and the compressive strength is 7.5MPa. It can be widely used in a variety of gypsum products and mortars, reducing the cost of building raw materials.
Smart Images

Figure BDA0005214489350000071 
Figure BDA0005214489350000072 
Figure BDA0005214489350000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of construction engineering, and in particular to a modified fluorgypsum and a preparation method and application thereof. Background Art
[0002] Fluorogypsum, also known as calcium fluoride gypsum, is a byproduct produced in the production of hydrogen fluoride. It is a solid waste mainly containing calcium sulfate produced by the reaction of sulfuric acid and fluorspar. Its main component is anhydrous calcium sulfate. Fluorogypsum mainly comes from inorganic fluorides, organic fluorides and other hydrogen fluoride manufacturers. Every ton of hydrogen fluoride produced produces about 3.5 tons of fluorogypsum, and the solid waste is considerable.
[0003] However, untreated fluorinated gypsum is often accompanied by unreacted CaF 2 and H 2 SO 4 , sometimes H 2 SO 4 A high content makes the discharged fluorgypsum acidic; in addition, the performance indicators of fluorgypsum are unstable and the color difference is large.
[0004] At present, the total amount of fluorinated gypsum discharged in my country is about 3 million tons per year. Compared with other gypsums, fluorinated gypsum is difficult to dissolve in water, has a slow hydration rate, low initial strength, and severe expansion. It cannot be used directly as a building material. Most of it can only be processed at the low end by stacking in yards, paving and landfilling, which wastes resources and cross-pollutes the environment. Therefore, the comprehensive utilization of fluorinated gypsum solid waste materials is beneficial to environmental protection, energy and resources conservation, and turning waste into treasure. It is in line with my country's basic national policy and sustainable development strategy of "carbon peak" and "carbon neutrality". Therefore, the research and utilization of fluorinated gypsum resources has important practical and valuable significance. Summary of the invention
[0005] In view of the above problems, the present application provides a modified fluorgypsum suitable for construction use and a preparation method thereof, as well as the application of the modified fluorgypsum in cement-based dry-mix masonry, plastering, sound insulation mortar, building thermal insulation mortar and gypsum-based lightweight plastering mortar materials. The present application opens up a new way for the recycling and comprehensive utilization of fluorgypsum, which not only reduces environmental pressure for society, but also creates the best economic benefits for enterprises.
[0006] The first aspect of the present application provides a method for preparing modified fluorgypsum, comprising the following steps:
[0007] S1: crushing the solid waste fluorgypsum and screening it through a 40-mesh sieve to obtain fluorgypsum particles;
[0008] S2: subjecting the fluorgypsum particles to an aging treatment to obtain aged fluorgypsum;
[0009] S3: mixing the aged fluorgypsum with sodium hydroxide and a naphthalene-based water reducer, and then mechanically grinding the mixed mixture to obtain the modified fluorgypsum.
[0010] Different from the prior art, the above technical solution provides a modified fluorgypsum. After the modified fluorgypsum is added with water to prepare a gel, the initial setting time is 3 hours, the final setting time is 15 hours, the flexural strength after 7 days is 3.5 MPa, and the compressive strength is 7.5 MPa. The modified fluorgypsum can be widely used as a cementitious material and filler in a variety of gypsum products and mortars, reducing the cost of construction raw materials.
[0011] Furthermore, the modified fluorgypsum contains 10wt% of sodium hydroxide and 1.5wt% of naphthalene-based water reducer.
[0012] Furthermore, the particle size of the modified fluorgypsum is 0.07-0.21 mm, of which fine powder below 0.15 mm accounts for 30%-40%.
[0013] Furthermore, the pH value of the modified fluorgypsum is 11.0-11.5.
[0014] The second aspect of the present application provides a modified fluorgypsum, which is prepared by the preparation method described in the first aspect of the present application.
[0015] The third aspect of the present application provides a masonry mortar, which comprises the following components in parts by mass: 130 parts by mass of cement, 670 parts by mass of sand, 250 parts by mass of the modified fluorgypsum described in the second aspect of the present application, 0.5 parts by mass of hydroxypropyl methylcellulose, 0.03 parts by mass of an air entraining agent, and 0.3 parts by mass of a stabilizer.
[0016] The fourth aspect of the present application provides a plaster mortar, which comprises the following components in parts by mass: 100 parts by mass of cement, 620 parts by mass of sand, 280 parts by mass of the modified fluorgypsum described in the second aspect of the present application, 0.7 parts by mass of hydroxypropyl methylcellulose, 0.03 parts by mass of an air entraining agent, and 0.3 parts by mass of a stabilizer.
[0017] In a fifth aspect of the present application, a sound-insulating mortar is provided, comprising the following components in parts by mass: 100 parts by mass of cement, 595 parts by mass of sand, 15 parts by mass of expanded perlite, 40 parts by mass of expanded clay, 250 parts by mass of the modified fluorgypsum described in the second aspect of the present application, and 2 parts by mass of hydroxypropyl methylcellulose.
[0018] The sixth aspect of the present application provides a plastering gypsum, which comprises the following components in parts by mass: 400 parts by mass of desulfurized gypsum, 300 parts by mass of the modified fluorinated gypsum described in the second aspect of the present application, 260 parts by mass of heavy calcium powder, 40 parts by mass of vitrified microspheres, 4 parts by mass of hydroxypropyl methylcellulose, 0.15 parts by mass of retarder, 0.3 parts by mass of starch ether, and 0.5 parts by mass of thixotropic lubricant.
[0019] The seventh aspect of the present application provides an inorganic thermal insulation mortar, which includes the following components in parts by mass: 80 parts by mass of cement, 100 parts by mass of the modified fluorgypsum described in the second aspect of the present application, 60 parts by mass of glass microspheres, 5 parts by mass of hydroxypropyl methylcellulose, 5 parts by mass of latex powder, 0.5 parts by mass of starch ether, 5 parts by mass of calcium formate, and 1.5 parts by mass of thixotropic lubricant.
[0020] The above-mentioned records related to the invention content are only an overview of the technical solution of the present application. In order to enable ordinary technicians in the field to more clearly understand the technical solution of the present application, and then implement it according to the written contents of the specification, and to make the above-mentioned purpose and other purposes, features and advantages of the present application easier to understand, the specific implementation methods of the present application are explained below. DETAILED DESCRIPTION
[0021] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments.
[0022] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects that can be achieved, the following is a detailed description in conjunction with the specific embodiments listed. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0023] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0024] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0025] In the description of this application, the term "and / or" is an expression used to describe the logical relationship between objects, indicating that three relationships may exist, for example, A and / or B, which means: A exists, B exists, and A and B exist at the same time. In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" logical relationship.
[0026] In the present application, terms such as “first” and “second” are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship of quantity, priority or sequence between these entities or operations.
[0027] Without further limitations, in this application, the words "include", "comprises", "has" or other similar expressions used in the sentences are intended to cover non-exclusive inclusion. These expressions do not exclude the presence of additional elements in the process, method or product including the elements, so that the process, method or product including a series of elements may include not only those limited elements, but also other elements not explicitly listed, or also include elements inherent to such process, method or product.
[0028] Similar to the understanding in the Examination Guidelines, in this application, expressions such as "greater than", "less than", "exceed" and the like are understood to exclude the number itself; expressions such as "above", "below", "within" and the like are understood to include the number itself. In addition, in the description of the embodiments of this application, "multiple" means more than two (including two), and similar expressions related to "multiple" are also understood in this way, such as "multiple groups", "multiple times", etc., unless otherwise clearly and specifically limited.
[0029] The first aspect of the present application provides a method for preparing modified fluorgypsum, comprising the following steps:
[0030] S1: crushing the solid waste fluorgypsum and screening it through a 40-mesh sieve to obtain fluorgypsum particles;
[0031] S2: subjecting the fluorgypsum particles to an aging treatment to obtain aged fluorgypsum;
[0032] S3: mixing the aged fluorgypsum with sodium hydroxide and a naphthalene-based water reducer, and then mechanically grinding the mixed mixture to obtain the modified fluorgypsum.
[0033] Different from the prior art, the above technical solution provides a modified fluorgypsum. After the modified fluorgypsum is added with water to prepare a gel, the initial setting time is 3 hours, the final setting time is 15 hours, the flexural strength after 7 days is 3.5 MPa, and the compressive strength is 7.5 MPa. The modified fluorgypsum can be widely used as a cementitious material and filler in a variety of gypsum products and mortars, reducing the cost of construction raw materials.
[0034] Fluorogypsum is tough and produces resistance during grinding, making it difficult to grind into fine powder. Sodium hydroxide can improve grinding efficiency and solidify free ions, increase the specific surface area of particles, and help dissolve and improve the hydration rate of modified fluorogypsum.
[0035] Naphthalene-based water reducer is adsorbed on the surface of fluorgypsum, reducing the agglomeration effect during the grinding process, playing a role in aiding grinding and dispersion, and increasing solubility.
[0036] After aging, the crystal structure of fluorinated gypsum decays from the original granular structure to a needle-like structure and a plate-like structure. The particles gradually change phase to produce strength, which is 0.5% higher than that of cement, and can be used as a building material. However, compared with other gypsums, modified fluorinated gypsum is difficult to dissolve in water, has a slow hydration rate, low initial strength, and severe expansion. It cannot be used directly as a building cementitious material. Other cementitious materials must be added to ensure its stability and safety.
[0037] Furthermore, the modified fluorgypsum contains 10wt% of sodium hydroxide and 1.5wt% of naphthalene-based water reducer.
[0038] Sodium hydroxide can improve the grinding efficiency and solidify the free ions, increase the specific surface area of the particles, and is conducive to dissolving and improving the hydration rate of modified fluorgypsum.
[0039] Naphthalene water reducer is adsorbed on the surface of fluorinated gypsum, reducing the agglomeration effect during the grinding process, playing a role in grinding and dispersion, and increasing solubility. When the dosage of naphthalene water reducer is 1.5%, the film formation and growth rate of the product dihydrate gypsum can reach a better level.
[0040] Furthermore, the particle size of the modified fluorgypsum is 0.07-0.21 mm, of which fine powder below 0.15 mm accounts for 30%-40%.
[0041] Furthermore, the pH value of the modified fluorgypsum is 11.0-11.5.
[0042] The second aspect of the present application provides a modified fluorgypsum, which is prepared by the preparation method described in the first aspect of the present application.
[0043] Furthermore, the water content of the modified fluorgypsum is 2-3%.
[0044] The third aspect of the present application provides a masonry mortar, which comprises the following components in parts by mass: 130 parts by mass of cement, 670 parts by mass of sand, 250 parts by mass of the modified fluorgypsum described in the second aspect of the present application, 0.5 parts by mass of hydroxypropyl methylcellulose, 0.03 parts by mass of an air entraining agent, and 0.3 parts by mass of a stabilizer.
[0045] The fourth aspect of the present application provides a plaster mortar, which comprises the following components in parts by mass: 100 parts by mass of cement, 620 parts by mass of sand, 280 parts by mass of the modified fluorgypsum described in the second aspect of the present application, 0.7 parts by mass of hydroxypropyl methylcellulose, 0.03 parts by mass of an air entraining agent, and 0.3 parts by mass of a stabilizer.
[0046] In a fifth aspect of the present application, a sound-insulating mortar is provided, comprising the following components in parts by mass: 100 parts by mass of cement, 595 parts by mass of sand, 15 parts by mass of expanded perlite, 40 parts by mass of expanded clay, 250 parts by mass of the modified fluorgypsum described in the second aspect of the present application, and 2 parts by mass of hydroxypropyl methylcellulose.
[0047] The sixth aspect of the present application provides a plastering gypsum, which comprises the following components in parts by mass: 400 parts by mass of desulfurized gypsum, 300 parts by mass of the modified fluorinated gypsum described in the second aspect of the present application, 260 parts by mass of heavy calcium powder, 40 parts by mass of vitrified microspheres, 4 parts by mass of hydroxypropyl methylcellulose, 0.15 parts by mass of retarder, 0.3 parts by mass of starch ether, and 0.5 parts by mass of thixotropic lubricant.
[0048] The seventh aspect of the present application provides an inorganic thermal insulation mortar, which includes the following components in parts by mass: 80 parts by mass of cement, 100 parts by mass of the modified fluorgypsum described in the second aspect of the present application, 60 parts by mass of glass microspheres, 5 parts by mass of hydroxypropyl methylcellulose, 5 parts by mass of latex powder, 0.5 parts by mass of starch ether, 5 parts by mass of calcium formate, and 1.5 parts by mass of thixotropic lubricant.
[0049] The raw material anhydrous fluorgypsum used in this embodiment is obtained by mechanically grinding the newly discharged fluorgypsum from the Longyan Shanghang Plant after cooling in the yard.
[0050] ① The chemical composition of raw material fluorgypsum is shown in Table 1
[0051] Table 1 Chemical composition of raw material fluorgypsum
[0052] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[Al 2 THE 3 ]]> CaO MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> content 1.55 2.28 1.12 36.40 0.10 0.18 0.13 chemical composition <![CDATA[TiO 2 ]]> <![CDATA[P 2 THE 5 ]]> MnO <![CDATA[Cr 2 THE 3 ]]> <![CDATA[SO 3 ]]> <![CDATA[CeO 2 ]]> <![CDATA[ZrO 2 (Zr+Hf)]]> content 0.02 3.52 0.08 0.03 49.7 0.99 0.00 chemical composition BaO SrO content 0.39 0.06
[0053] The cement used in this embodiment is ordinary Portland cement (P.O42.5) produced by Longyan Hualong Cement Plant, and its specific properties are shown in Table 2.
[0054] Table 2 Physical properties of ordinary Portland cement
[0055]
[0056] ①Inspection basis: GB 175-2023 "General Portland Cement"
[0057] ②Test methods: GB / T 17671-2021 "Test method for strength of cement mortar", GB / T 750-1992 "Test method for stability of cement autoclave", GB / T 8074-2008 "Determination method for specific surface area of cement", GB / T 1346-2011 "Water consumption for standard consistency of cement"
[0058] ③Inspection conclusion: After testing, the physical performance indicators of the P.O42.5 cement can meet the technical index requirements of cement-fluorinated gypsum mixed masonry, plastering, sound insulation and other mortars.
[0059] In this embodiment, the artificial machine-made sand used is medium sand produced by Longyan Hongjianshan New Building Materials Co., Ltd., and its material properties are shown in Table 3.
[0060] Table 3 Physical properties of artificial sand
[0061]
[0062] ①Test basis: GB / T 14684-2022 "Construction Sand"
[0063] ②Test method: GB / T 14684-2022 "Construction sand"
[0064] ③Inspection conclusion: After testing, the physical performance indicators of the artificial sand can meet the technical index requirements of cement fluorite gypsum mixed mortar.
[0065] In this embodiment, the artificial mechanism fine sand used is the fine sand produced by Longyan Hongjianshan New Building Materials Co., Ltd., and its physical properties are shown in Table 4.
[0066] Table 4 Physical performance indexes of artificial fine sand
[0067]
[0068] ①Test basis: GB / T 14684-2022 "Construction Sand"
[0069] ②Test method: GB / T 14684-2022
[0070] ③Test conclusion: After testing, it is found that the physical properties of the artificial sand used in cement-fluorinated gypsum mixed mortar can meet the technical requirements of cement-fluorinated gypsum mixed mortar.
[0071] The vitrified microspheres used in this embodiment are a type of vitrified microspheres produced in Xinyang, Henan Province, and their physical performance indicators are shown in Table 5.
[0072] Table 5 Physical performance indexes of vitrified microspheres
[0073]
[0074] ① Implementation standard: JC / T 1042-2007 "Expanded Vitrified Microspheres"
[0075] ②Test method: GB / T 17431.2, JC / T 1042, GB / T 10294
[0076] ③Test conclusion: After testing, it is found that the physical performance indicators of the vitrified microspheres used in cement-fluorinated gypsum mixed mortar can meet the technical requirements of cement-fluorinated gypsum mixed mortar.
[0077] The main experimental instruments and equipment used in this embodiment include: ① servo electro-hydraulic anti-bending and anti-compression integrated machine (TYA-300 model) ② cement mortar mixer (JJ5) ③ mortar mixer (VJZ-15) ④ mortar consistency meter (SZ-145) ⑤ mortar water retention rate tester (P100×25mm) ⑥ mortar setting time tester (ZKS-100) ⑦ mortar shrinkage tester (SP-175) ⑧ mortar bond strength puller (DL-5000) ⑨ gypsum-based mortar water retention rate tester ⑩ experimental ball mill (SM500×500mm) Vibration mill (model GJ-II) X-ray diffractometer (RIGAKU, Japan)
[0078] Example 1 Proportion Test
[0079] S1: crushing the solid waste fluorgypsum and screening it through a 40-mesh sieve to obtain fluorgypsum particles;
[0080] S2: subjecting the fluorgypsum particles to an aging treatment to obtain aged fluorgypsum;
[0081] S3: mixing the aged fluorgypsum with sodium hydroxide and a naphthalene-based water reducer, and then mechanically grinding the mixed mixture to obtain the modified fluorgypsum.
[0082] S4: adding modified fluorgypsum to water and mixing to reach a standard consistency to obtain a fluorgypsum gel material.
[0083] Test 1: The addition amount of sodium hydroxide was (3%, 5%, 10%, 15%, 20%), and the addition amount of naphthalene-based water reducer was 1.0%;
[0084] Test 2: The addition amount of naphthalene-based water reducer was (0.5%, 1.0%, 1.5%, 1.8%, 2.0%), and the addition amount of sodium hydroxide was 10%.
[0085] Test method:
[0086] The setting time of fluorinated gypsum gel material is determined according to the method of GB 1346-2001.
[0087] The flexural and compressive strength of fluorinated gypsum gel materials are tested in accordance with GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)".
[0088] The test results show that with the increase of sodium hydroxide and naphthalene-based water reducer, the setting time of modified fluorgypsum gel continues to decrease. When the sodium hydroxide dosage is greater than 10% or the naphthalene-based water reducer dosage is greater than 1.5%, the setting time of modified fluorgypsum gel increases sharply.
[0089] When the sodium hydroxide content is 10% and the naphthalene water reducer content is 1.5%, the initial setting time is shortened to 3h and the final setting time is shortened to 15h. According to the initial setting time of unmodified fluorinated gypsum gel of 24h and the final setting time of 48h, after adding 10% sodium hydroxide and 1.5% naphthalene water reducer, the initial setting time of modified fluorinated gypsum gel decreased by 87.3% and the final setting time decreased by 91.0%; the measured pH value is alkaline (11.39), and the water consumption of standard consistency is 21.7%.
[0090] When the sodium hydroxide dosage is 10% and the naphthalene-based water-reducing agent dosage is 1.5%, the flexural and compressive strengths of the modified fluorinated gypsum gel are: after testing for 7 days, the flexural strength reaches 3.5MPa and the compressive strength reaches 7.5MPa respectively.
[0091] Through the flexural and compressive tests, it can be seen that the addition of sodium hydroxide and naphthalene-based water reducers to fluorinated gypsum solid waste materials can improve the flexural and compressive strength of modified fluorinated gypsum gel materials. Therefore, sodium hydroxide and naphthalene-based water reducers are the best activators for fluorinated gypsum solid waste raw materials.
[0092] Example 2 Preparation of modified fluorgypsum
[0093] S1: crushing the raw material fluorgypsum and screening it through a 40-mesh sieve to obtain fluorgypsum particles;
[0094] S2: subjecting the fluorgypsum particles to an aging treatment to obtain aged fluorgypsum;
[0095] S3: Mixing the aged fluorgypsum with 10%wt sodium hydroxide and 1.5wt% naphthalene-based water reducer, and then mechanically grinding the mixture until uniform, to obtain the modified fluorgypsum.
[0096] The fineness of the modified fluorgypsum after mechanical grinding is shown in Table 6. The density of the modified fluorgypsum is 2.81 g / cm 3 Specific surface area: 610m 2 / kg.
[0097] Table 6 Fineness of modified fluorgypsum
[0098] Screen aperture / mesh 8 14 48 100 200 Screen residue / g 0 0.4 131 168 187 Screen residue / % 0 0.08 26.2 33.6 37.4
[0099] Example 3 Experimental study on preparing masonry mortar by adding modified fluorgypsum to dry-mixed masonry mortar
[0100] ① Implementation standard: GB / T 25181-2019 "Premixed Mortar"
[0101] ②Test method: JGJ / T 70-2009 "Test method for basic properties of building mortar"
[0102] ③ Raw material preparation and quality control: First, it is necessary to determine the types and proportions of cement, sand, modified fluorgypsum, fillers and other additives required for the test, and then test various raw materials in accordance with national standards. Because the quality of raw materials directly affects the strength and durability of masonry and plastering mortar, the performance indicators of raw materials must meet the technical requirements for preparing dry-mixed masonry and plastering mortar.
[0103] ④ Design the mix ratios of dry-mixed masonry mortar and masonry mortar prepared with modified fluorgypsum: According to the national industry standard: JGJ / T 98-2010 "Design Code for Mix Ratio of Masonry Mortar", the design mix ratio is shown in Table 7 (Mortar Type: DMM7.5)
[0104] ⑤ The comparative test results of the performance indicators of dry-mixed masonry mortar and masonry mortar prepared with modified fluorgypsum are shown in Table 8
[0105] Table 7 Mix ratios of dry-mixed masonry mortar and masonry mortar prepared by adding modified fluorgypsum
[0106]
[0107] Table 8 Comparative test table of dry-mixed masonry mortar and masonry mortar prepared with modified fluorgypsum
[0108]
[0109] ⑥a. The above test results are the average test data of the test performance index results of 15 groups of dry-mixed masonry mortar and masonry mortar prepared with modified fluorgypsum.
[0110] b. Test conclusion: The physical properties of dry-mixed masonry mortar and masonry mortar prepared with modified fluorgypsum were tested in accordance with JGJ / T 70-2009 "Test methods for basic properties of building mortar". The performance indicators of both are in line with the performance indicators stipulated by the state, so the masonry mortars prepared with this mix ratio are qualified.
[0111] Example 4 Experimental study on plaster mortar prepared by adding modified fluorgypsum to dry-mixed plaster mortar
[0112] ① Implementation standard: GB / T 25181-2019 "Premixed Mortar"
[0113] ②Test method: JGJ / T 70-2009 "Test method for basic properties of building mortar"
[0114] ③ Raw material preparation and quality control: First, it is necessary to determine the types and proportions of cement, sand, modified fluorgypsum, fillers and other additives required for the test, and then test various raw materials in accordance with national standards. Because the quality of raw materials directly affects the strength and durability of plaster mortar, the performance indicators of raw materials must meet the technical requirements for preparing dry-mixed plaster mortar.
[0115] ④ Design the mix ratios of dry-mixed plaster mortar and plaster mortar prepared with modified fluorgypsum: According to the national industry standard: JGJ 220-2010 "Technical Specifications for Plaster Mortar", the design mix ratios are shown in Table 9 (Mortar Type: DPM7.5)
[0116] ⑤ The comparison test results of the physical properties of dry-mixed plaster mortar and plaster mortar prepared with modified fluorgypsum are shown in Table 10
[0117] Table 9 Mixing ratios of dry-mixed plaster mortar and plaster mortar prepared with modified fluorgypsum
[0118]
[0119] Table 10 Comparative test results of physical properties of dry-mixed plaster mortar and plaster mortar prepared with modified fluorgypsum
[0120]
[0121] ⑥a. The above test results are the average test data of the performance index results of 15 groups of dry-mixed plaster mortars and plaster mortars prepared with modified fluorgypsum.
[0122] b. Test conclusion: The physical properties of dry-mixed plaster mortar and plaster mortar prepared with modified fluorgypsum were tested in accordance with JGJ / T 70-2009 "Test Methods for Basic Properties of Building Mortar". The performance indicators of both are in line with the performance indicators specified in the national standards. Therefore, the plaster mortars prepared with this mix ratio are qualified.
[0123] Example 5 Experimental study on preparing sound insulation mortar by adding modified fluorgypsum to dry-mixed sound insulation mortar
[0124] ① Implementation standard: JC / T 2707-2022 "Sound insulation mortar"
[0125] ②Test method: JGJ / T 70-2009 "Test method for basic properties of building mortar", GB / T20473-2021 "Building thermal insulation mortar", GB / T19889.9-2006 Acoustics, sound insulation measurement of buildings and building components Part 8: Laboratory measurement of impact sound improvement of heavy standard floor coverings.
[0126] ③ Raw material preparation and quality control: First determine the types and proportions of cement, sand, modified fluorgypsum, lightweight aggregate, fillers and additives required for the test, and then test the various raw materials in accordance with national standards. The quality of the raw materials directly affects the sound insulation effect, durability and strength of the sound insulation mortar, so the performance indicators of the raw materials must meet the technical requirements for the preparation of sound insulation mortar.
[0127] ④ Design the mix ratios of dry-mixed sound insulation mortar and sound insulation mortar prepared by adding modified fluorinated gypsum: According to the national industry standard JC / T 2707-2022 "Sound insulation mortar", the design mix ratios are shown in Table 11
[0128] ⑤ The comparative test results of the physical performance indicators of dry-mixed sound insulation mortar and sound insulation mortar prepared by adding modified fluorinated gypsum are shown in Table 12
[0129] Table 11 Proportions of dry-mixed sound insulation mortar and sound insulation mortar prepared with additive-modified fluorinated gypsum
[0130]
[0131]
[0132] Table 12 Comparative test results of physical properties of mixed sound insulation mortar and sound insulation mortar prepared with modified fluorgypsum
[0133]
[0134] ⑥a. The above test results are the average test data of the performance index results of 15 groups of dry-mixed sound insulation mortar and sound insulation mortar prepared with additive-modified fluorinated gypsum.
[0135] b. Inspection conclusion: The performance indicators of dry-mixed sound insulation mortar and sound insulation mortar prepared with additive-modified fluorinated gypsum were tested according to the test methods of JGJ / T 70-2009, GB / T20473-2021 and GB / T19889.8-2006. The performance indicators are in line with the technical indicators prescribed by the state. Therefore, the sound insulation mortars prepared with this formula are qualified.
[0136] Example 6. Experimental study on preparing plastering gypsum by adding modified fluorgypsum to gypsum-based lightweight plastering mortar
[0137] ① Implementation standard: GB / T 28627-2023 "Plastering gypsum"
[0138] ②Test methods: GB / T 1346-2011 "Test methods for water consumption, setting time and stability of cement standard consistency", GB / T 17671-2021 "Test methods for strength of cement mortar", GB / T 5484-2024 "Chemical analysis methods for gypsum".
[0139] ③ Raw material preparation and quality control: First, determine the types and proportions of desulfurized gypsum, fluorinated gypsum, heavy calcium powder, vitrified microspheres and functional additives required for the test, and then test the various raw materials in accordance with national standards to ensure the strength and durability of the gypsum lightweight plaster mortar. The performance indicators of the raw materials must meet the technical requirements for the preparation of gypsum lightweight plaster mortar.
[0140] ④ Design the mix ratio of lightweight gypsum plastering mortar and lightweight gypsum plastering mortar prepared by adding modified fluorgypsum (see Table 13 below)
[0141] Table 13 Proportions of lightweight plaster gypsum mortar and gypsum-based lightweight plaster mortar prepared with modified fluorgypsum
[0142]
[0143] ⑤ Comparative test results of physical properties of gypsum-based lightweight plaster mortar and gypsum-based lightweight plaster mortar prepared with modified fluorgypsum (see Table 14)
[0144] Table 14 Comparison of physical properties of gypsum-based lightweight plaster mortar and gypsum-based lightweight plaster mortar prepared with modified fluorgypsum
[0145]
[0146] ⑥a. The above test results are the average test data of the performance index results of 15 groups of lightweight plaster gypsum mortars and lightweight plaster gypsum mortars prepared with modified fluorgypsum.
[0147] b. Test conclusion: According to the test methods of GB / T 1346-2011, GB / T 17671-2021 and GB / T 5484-2024, the performance indexes of lightweight plaster gypsum mortar and lightweight plaster gypsum mortar prepared by adding modified fluorgypsum were tested and tested. The performance indexes of both of them meet the technical indexes stipulated by the state. Therefore, the lightweight plaster gypsum mortar prepared by this formula is qualified.
[0148] Example 7. Experimental study on inorganic building thermal insulation mortar prepared by adding modified fluorgypsum
[0149] ① Implementation standard: GB / T 20473-2021 "Building thermal insulation mortar"
[0150] ②Test methods: GB / T 20473-2021 "Building thermal insulation mortar", GB / T 5486-2008 "Test methods for inorganic rigid insulation products", GB / T 10294-2008 "Determination of steady-state thermal resistance and related properties of insulation materials - Guarded hot plate method", JGJ / T 70-2009 "Test methods for basic properties of building mortar"
[0151] ③ Raw material preparation and quality control: First determine the types and proportions of cement, fluorgypsum, fly ash, vitrified microspheres and functional additives required for the test, and then test the various raw materials in accordance with national standards. The quality of the raw materials directly affects the thermal insulation effect, strength and durability of the building insulation mortar, so the performance indicators of the raw materials must meet the technical requirements for the preparation of inorganic building insulation mortar.
[0152] ④ Design the mix ratios of inorganic building insulation mortar and inorganic building insulation mortar prepared with modified fluorgypsum: According to the national standard: GB / T 20473-2021 "Building Insulation Mortar" design mix ratio (see Table 15, inorganic insulation mortar model: Type II) Table 15 Mix ratios of inorganic building insulation mortar and inorganic building insulation mortar prepared with modified fluorgypsum
[0153]
[0154]
[0155] ⑤ Test results of physical performance indicators of inorganic building thermal insulation mortar and inorganic building thermal insulation mortar prepared with modified fluorgypsum (see Table 16, inorganic thermal insulation mortar model: Type II)
[0156] Table 16 Test results of physical properties of inorganic building insulation mortar and inorganic building insulation mortar prepared with modified fluorinated gypsum
[0157]
[0158] ⑥a. The above test results are the average test data of the performance indicators of 15 groups of inorganic building insulation mortars and inorganic building insulation mortars prepared with modified fluorgypsum.
[0159] b. Test conclusion: The performance indexes of inorganic building thermal insulation mortar and inorganic building thermal insulation mortar with modified fluorgypsum were tested according to the test methods of GB / T 20473-2021, GB / T 5486-2008, GB / T 10294-2008 and JGJ / T70-2009. The performance indexes of inorganic building thermal insulation mortar and inorganic building thermal insulation mortar with modified fluorgypsum meet the technical indexes stipulated by the state. Therefore, the inorganic building thermal insulation mortar prepared by this mix ratio is qualified.
[0160] This application research strictly prepares various types of masonry, plastering, sound insulation mortars, gypsum-based lightweight plastering mortars and inorganic building insulation mortars with modified fluorgypsum in accordance with national standards. A series of comparative tests are conducted to test the physical performance indicators of various types of mortars.
[0161] First, the strength of various types of mortars is generally 0.7-0.9MPa higher than the average strength of traditional mortars; the tensile bond strength is increased by 0.2-0.3MPa, thus ensuring the compressive strength and tensile bond strength of various types of mortars. Second, the various types of mortars prepared have a certain self-water retention function due to the addition of modified fluorgypsum, so the water retention rate is increased by 2 percentage points, ensuring the normal hardening and maintenance needs of various types of mortars. Third, the various types of mortars prepared have delayed the opening time due to the addition of modified fluorgypsum, and the 2h consistency loss rate is less than 15%. It is especially suitable for plastering in the south due to high temperature. Fourth, the various types of mortars prepared have added modified fluorgypsum, because the density of fluorgypsum itself is light, the wet apparent density is 60-80kg lower per cubic meter than the various types of mortars prepared by traditional methods, and the plasticizing effect is very obvious, the lubrication is good, and the construction performance is excellent. Fifth, due to the addition of modified fluorgypsum, the setting time of fluorgypsum itself is relatively slow and the increase in the amount of addition causes the setting time to be longer, but it does not affect the overall quality of various types of mortars, and is safe and reliable in application. The above is a summary of the comparative analysis of various types of mortars prepared by adding modified fluorgypsum. The quality of mortar is one of the focuses of the construction industry. Through a series of adjustments to the mix ratio test, the quality environment of the mortar can be better grasped, providing a strong guarantee for the safety and durability of the project.
[0162] The successful application of fluorinated gypsum solid waste resources in various types of mortars has opened up a new path for the utilization of fluorinated gypsum solid waste. Its advantages include the following aspects: First, environmental protection and energy saving: the main raw material of fluorinated gypsum, industrial waste slag, is made by alumina process. Compared with traditional cement, it reduces a large number of raw material sintering processes in the mining industry, thereby greatly reducing environmental pollution and energy waste. Second, resource recycling. Fluorinated gypsum solid waste can replace primary mineral resources, achieve source reduction and harm reduction, and resource and environmental utilization, which is of great significance for building a resource-saving and environmentally friendly industrial system. Third, reduce environmental pollution: The utilization of fluorinated gypsum can reduce the utilization of industrial by-product gypsum, avoid pollution and safety hazards to the environment. Fourth: Economic benefits: The utilization of fluorinated gypsum solid waste can replace part of the cement usage, reduce construction costs, and improve the economic benefits of enterprises. In short, the utilization of fluorinated gypsum solid waste not only helps environmental protection and energy saving, but also brings significant economic and social benefits.
[0163] Finally, it should be noted that although the above embodiments have been described in the text of the specification of this application, this does not limit the scope of patent protection of this application. All technical solutions generated by replacing or modifying equivalent structures or equivalent processes based on the essential concept of this application using the contents recorded in the text of the specification of this application, as well as directly or indirectly implementing the technical solutions of the above embodiments in other related technical fields, are included in the scope of patent protection of this application.
Claims
1. A method for preparing modified fluorgypsum, characterized in that: The following steps are involved: S1: crushing the solid waste fluorgypsum and screening it through a 40-mesh sieve to obtain fluorgypsum particles; S2: subjecting the fluorgypsum particles to an aging treatment to obtain aged fluorgypsum; S3: mixing the aged fluorgypsum with sodium hydroxide and a naphthalene-based water reducer, and then mechanically grinding the mixed mixture to obtain the modified fluorgypsum.
2. The preparation method according to claim 1, characterized in that: The modified fluorgypsum contains 10 wt% of sodium hydroxide and 1.5 wt% of naphthalene-based water reducer.
3. The method for preparing modified fluorgypsum according to claim 1, characterized in that: The particle size of the modified fluorgypsum is 0.07-0.21 mm, of which fine powder below 0.15 mm accounts for 30%-40%.
4. The method for preparing modified fluorgypsum according to claim 1, characterized in that: The pH value of the modified fluorgypsum is 11.0-11.
5.
5. A modified fluorgypsum, characterized in that: The modified fluorgypsum is prepared by the preparation method according to any one of claims 1 to 4.
6. A masonry mortar, characterized in that: The masonry mortar comprises the following components in parts by mass: 130 parts by mass of cement, 670 parts by mass of sand, 250 parts by mass of the modified fluorgypsum as claimed in claim 5, 0.5 parts by mass of hydroxypropyl methylcellulose, 0.03 parts by mass of air entraining agent, and 0.3 parts by mass of stabilizer.
7. A plastering mortar, characterized in that: The plaster mortar comprises the following components in parts by mass: 100 parts by mass of cement, 620 parts by mass of sand, 280 parts by mass of the modified fluorgypsum according to claim 5, 0.7 parts by mass of hydroxypropyl methylcellulose, 0.03 parts by mass of air entraining agent, and 0.3 parts by mass of stabilizer.
8. A sound insulation mortar, characterized in that: The sound insulation mortar comprises the following components in parts by mass: 100 parts by mass of cement, 595 parts by mass of sand, 15 parts by mass of expanded perlite, 40 parts by mass of ceramsite, 250 parts by mass of the modified fluorgypsum according to claim 5, and 2 parts by mass of hydroxypropyl methylcellulose.
9. A plastering gypsum, characterized in that: The plastering gypsum comprises the following components in parts by mass: 400 parts by mass of desulfurized gypsum, 300 parts by mass of the modified fluorinated gypsum according to claim 5, 260 parts by mass of heavy calcium powder, 40 parts by mass of vitrified microspheres, 4 parts by mass of hydroxypropyl methylcellulose, 0.15 parts by mass of retarder, 0.3 parts by mass of starch ether, and 0.5 parts by mass of thixotropic lubricant.
10. An inorganic thermal insulation mortar, characterized in that: The inorganic thermal insulation mortar comprises the following components in parts by mass: 80 parts by mass of cement, 100 parts by mass of the modified fluorgypsum as claimed in claim 5, 60 parts by mass of vitrified microspheres, 5 parts by mass of hydroxypropyl methylcellulose, 5 parts by mass of latex powder, 0.5 parts by mass of starch ether, 5 parts by mass of calcium formate, and 1.5 parts by mass of thixotropic lubricant.